A comprehensive study on lignin as a green alternative of silica in natural rubber composites. (September 2016) - Yu, Peng; He, Hui; Jia, Yunchao; Tian, Shenghui; Chen, Jian; Jia, Demin; Luo, Yuanfang
Abstract: Using waste materials in polymeric products has drawn great attention over the recent years for economic and environmental concerns. Lignin, which is byproducts of paper-making industry, can be used as a valuable rubber filler. Silica is one of main fillers in rubber industry. Since using two different filler may exhibit some synergistic effects in polymers by making full use of each filler's advantage and character. In this research, we investigated the influence of lignin/silica hybrid filler towards natural rubber. The results revealed that the partial replacement of silica by lignin in the blends did not severely deteriorate mechanical properties of the composites. Besides, the inclusion of lignin into the rubber could not only weaken the Payne effect but also improve the processability, anti-aging resistance and anti-flex cracking of composites. The vulcanizate containing 20 phr lignin and 30 phr of silica in hybrid filler exhibited the optimal overall mechanical properties.